Kinetic models of candle shell alkaline hydrolysis in obtaining oxalic acid - Siswanto; Kindriari Nurma Wahyusi; Renova Panjaitan; Ardika Nurmawati; Ellen Oktavia Hanim Najakha (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
The kinetic reaction of alkaline hydrolysis of candlenut shells to produce oxalic acid was investigated. It was performed for the non-catalyzed solid-liquid heterogeneous reaction in a range time of 30 to 90 minutes and temperature of 60oC to 90oC. This study showed that the reaction fitted the pseudo-first-order model, confirmed from the determinant coefficient value of 0.9182 to 0.9751, and the kinetic constant, evaluated using Arrhenius' law, was k= 0.034751 e^(-140.23⁄T). The rate control mechanism based on the shrinking core model was diffusion control, validated from determinant coefficient near one, from 0.9246 to 0.9766.